Analysis method for section structure of high-temperature oxide skin of iron-chromium-aluminum stainless steel plate

Through the combination of argon ion cross-section polishing technology, scanning electron microscope backscattering electron atomic number imaging technology and EBSD technology, the problem of high-temperature oxide scale cross-sectional structure analysis of iron-chromium aluminum stainless steel plates is solved, and the thickness of the oxide layer, phase structure and crystal are realized. Detailed analysis of particle morphology.

CN119438270APending Publication Date: 2025-02-14SHANXI TAIGANG STAINLESS STEEL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411279015.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The prior art is difficult to accurately analyze the thickness, phase structure and grain morphology of high-temperature oxide scale from the cross-sectional structure of iron-chromium aluminum stainless steel sheets.

Method used

Argon ion cross-section polishing technology combined with scanning electron microscope backscattered electron atomic number imaging technology and electron backscattered diffraction (EBSD) technology are used to realize detailed analysis of the high-temperature oxide scale cross-section structure of iron-chromium aluminum stainless steel plates.

Benefits of technology

Through this method, clear and complete oxide layer cross-sectional images can be obtained, the oxide layer thickness can be accurately measured, and crystal orientation measurement and phase calibration can be carried out to achieve a perfect analysis of the high-temperature oxide scale cross-sectional structure of iron-chromium aluminum stainless steel sheets.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a method for analyzing a high-temperature oxide skin structure of an iron-chromium-aluminum stainless steel plate, which integrates an argon ion section polishing technology, a scanning electron microscope backscattered electron atomic number contrast imaging technology and an electron backscattered diffraction (EBSD) technology. The method can realize section thickness measurement, phase analysis and oxide layer grain morphology and size analysis of the iron-chromium-aluminum stainless steel plate high-temperature oxide skin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of stainless steel material analysis and detection, and in particular to a method for analyzing the cross-sectional structure of high-temperature oxide scale of an iron-chromium-aluminum stainless steel plate. Background Art

[0002] Fe-Cr-Al stainless steel is an electric heating alloy material. At high temperatures, the alloy can form a protective layer of aluminum oxide, chromium oxide or composite oxide film on its surface, which makes it resistant to oxidation, carburization, sulfur and hydrogen gas corrosion at high temperatures. Commonly used Fe-Cr-Al alloy materials include 0Cr25Al5, 0Cr21A16 and 0Cr27Al7Mo2. Iron-chromium-aluminum electric heating alloy is a functional material with high cost performance and important uses. It has the advantages of high operating temperature, long life and low price. It is widely used in electric heating, industrial furnaces, food machinery, household appliances, environmental protection equipment manufacturing, automobile exhaust purification systems and other fields.

[0003] The Al2O3 generated by oxidation on the surface of Fe-Cr-Al alloy material has a dense structure, good adhesion to the substrate, and good bonding. Al2O3 has high resistivity and high melting point. These factors determine that the Al2O3 oxide film has excellent oxidation resistance.

[0004] There are many methods and means to analyze the composition and structure of high-temperature oxide scale on the surface of iron-chromium-aluminum stainless steel plates. Commonly used methods include: using optical microscopes and scanning electron microscopes to observe the surface morphology of oxide scales, using X-ray energy spectrometers to analyze the composition of oxide scales, and using X-ray diffractometers to analyze the physical structure of oxide scales. Due to the excellent oxidation resistance of iron-chromium-aluminum stainless steel, the thickness of the oxide scale formed even at high temperatures is relatively thin. Therefore, it is difficult to observe and analyze the structural composition of the oxide scale from the cross section of the plate.

[0005] The purpose of the present invention is to find a method for analyzing the cross-sectional composition structure of high-temperature oxide scale on the surface of an iron-chromium-aluminum stainless steel plate, and to achieve measurement of the thickness of the high-temperature oxide scale of the iron-chromium-aluminum stainless steel plate, phase analysis, and analysis of the oxide layer grain morphology and size from the cross section. Summary of the invention

[0006] The purpose of the present invention is to provide a method for analyzing the cross-sectional structure of high-temperature oxide scale of an iron-chromium-aluminum stainless steel plate in view of the above problems.

[0007] The object of the present invention is achieved as follows: a method for analyzing the cross-sectional structure of high-temperature oxide scale of an iron-chromium-aluminum stainless steel plate, comprising the following steps: step 1: cutting a sample of the iron-chromium-aluminum stainless steel plate after high-temperature oxidation by a wire cutting method; step 2: arbitrarily selecting a cross section for mechanical polishing; step 3: using an ultrasonic cleaning machine to clean the sample with anhydrous ethanol with a concentration of ≥99.7% analytical pure for 2-5 minutes, and then taking it out to dry naturally or with a hair dryer; step 4: using an argon ion cross-sectional polishing instrument to polish the argon ions of the mechanically polished cross section, the parameters of the argon ion polishing are as follows: acceleration voltage: 8-10KV, sample chamber vacuum: 1×10 -4 Pa-4×10 -4 Pa, the argon gas flow rate is 1.0-3.0L / min, and the polishing time is 30-60 minutes; Step 5: Fix the sample after argon ion polishing on the sample stage of the scanning electron microscope with the polished surface facing up, and use backscattered electrons for imaging. Due to the thin thickness of the oxide layer, it is necessary to take pictures at 5000-20000 times to obtain an atomic number contrast image; Step 6: Fix the sample after argon ion polishing on a sample stage pre-tilted at 70 degrees, and perform EBSD test of the oxide layer under a scanning electron microscope to analyze the phase composition and grain size. Parameter selection: acceleration voltage 20KV, probe current 6.4nA-26nA, magnification 5000-20000 times, and measurement step length 0.02-0.1 microns.

[0008] In step 1, the temperature of high temperature oxidation is 900° C.-1300° C., the oxidation time is 100 hours-1000 hours, and the sample length is 8-12 mm and the width is 8-12 mm.

[0009] The beneficial effects of the present invention are as follows: the present invention adopts argon ion cross-section polishing sample preparation technology to obtain a complete, undamaged oxide layer cross section, and on this basis, the scanning electron microscope backscattered electron atomic number contrast imaging technology can be used to obtain an oxide layer image with obvious contrast and clear boundaries, which is convenient and accurate to measure the thickness of the oxide layer, and the crystal orientation measurement and phase calibration of the oxide layer by electron backscattered diffraction (EBSD) technology can be used to obtain the composition and grain morphology size of the oxide layer, thereby achieving a perfect analysis of the cross-sectional structure of the high-temperature oxide scale of the iron-chromium-aluminum stainless steel plate. DETAILED DESCRIPTION

[0010] The present invention is based on the organic integration of (1) argon ion cross-section polishing sample preparation technology, (2) scanning electron microscope backscattered electron atomic number contrast imaging technology, and (3) electron backscatter diffraction (EBSD) technology to achieve high-temperature oxide scale cross-section thickness measurement and structural analysis of iron-chromium-aluminum stainless steel plates.

[0011] Due to the excellent oxidation resistance of iron-chromium-aluminum stainless steel, the thickness of the oxide scale formed at high temperature is also thin, and it is difficult to observe and analyze the structural composition of the oxide scale from the cross section of the plate. The traditional mechanical polishing method is not easy to protect the edge, resulting in inaccurate thickness detection, and the surface stress layer caused by mechanical polishing cannot be analyzed by EBSD structure.

[0012] The use of argon ion cross-section polishing technology can avoid the shortcomings of mechanical polishing. Argon ion polishing uses a high-voltage electric field to ionize argon gas to produce an ion state. The generated argon ions bombard the sample surface at high speed under the action of the acceleration voltage, and the sample is stripped layer by layer to achieve the polishing effect. Argon ion polishing technology polishes the sample surface and removes the damaged layer, which can obtain high-quality samples with a smooth surface, few scratches and damage, and clear boundaries. It is used for subsequent scanning electron microscopy imaging and EBSD analysis.

[0013] Since the oxide scale of iron-chromium-aluminum stainless steel is mainly composed of aluminum oxide, whose average atomic number is lower than that of the stainless steel matrix, the thickness of the oxide scale can be measured and analyzed using the scanning electron microscope backscattered electron atomic number imaging technology. The structure of the oxide scale and the morphology and size of the aluminum oxide grains can be analyzed using the electron backscattered diffraction (EBSD) technology.

[0014] Through the combination of the above three technologies, the cross-sectional composition structure of the high-temperature oxide scale on the surface of iron-chromium-aluminum stainless steel plates can be effectively analyzed.

[0015] The specific implementation process is as follows: 1. Cut a sample of length (8-12mm) × width (8-12mm) × plate thickness from the high-temperature oxidized iron-chromium-aluminum stainless steel plate.

[0016] 2. Select any cross section for mechanical polishing, and use 400, 800, 1200, and 2000 sandpaper for coarse grinding and fine grinding, and finally use 1μm diamond polishing paste for polishing until the observation surface presents a mirror-like smooth effect.

[0017] 3. Use an ultrasonic cleaner to clean the sample with anhydrous ethanol of analytical purity ≥99.7% for about 2 minutes. After taking it out, let it air dry naturally or use a hair dryer to dry it. The frequency of the ultrasonic cleaner is 40KHz.

[0018] 4. Use an argon ion cross-section polisher to perform argon ion polishing of the mechanically polished cross section. The main parameters of argon ion polishing include: (1) acceleration voltage: 8-10KV, (2) sample chamber vacuum: 4×10 -4 Pa, (3) the argon gas flow should be optimized, (4) the sample stage swing mode should be turned on, and (5) the polishing time should be selected so that the oxide scale on the cross section is completely exposed.

[0019] 5. Fix the sample after argon ion polishing on the sample stage of the scanning electron microscope with the polished surface facing up. Use backscattered electrons for imaging. Due to the thin thickness of the oxide layer, it is necessary to take pictures at a magnification of more than 5000 times to obtain an atomic number contrast image. In the image, the oxide layer is darker than the substrate and has a clear boundary with the stainless steel substrate, so it is easy to measure the thickness of the oxide layer.

[0020] 6. The sample after argon ion polishing was fixed on a sample stage pre-tilted at 70 degrees, and the EBSD test of the oxide layer was performed under a scanning electron microscope to analyze the phase composition and grain size. The main parameter selections include: (1) acceleration voltage 20KV, (2) probe current greater than 5nA, (3) magnification greater than 5000 times, (4) measurement step size less than 0.1 micron, (5) calibration phase selection Fe-Bcc and Alumina (alpha), etc. Example 1

[0021] Analysis of the cross-sectional structure of the oxide scale on 0Cr21Al6RE cold-rolled stainless steel sheet after being kept at 1000℃ for 500 hours.

[0022] 0Cr21Al6RE is an iron-chromium-aluminum stainless steel with trace rare earth (La and Ce) elements added. An oxidation experiment was carried out in the laboratory using 1.0mm thick 0Cr21Al6RE stainless steel cold-rolled plates at 1000℃ for 500 hours. The plates were then taken out and air-cooled. The surface morphology and composition of the oxide scale were first analyzed using a scanning electron microscope and an energy spectrometer.

[0023] The cross-sectional structure of the oxide scale is analyzed by the present invention, and the specific process is as follows: 1. Cut the 1.0 mm 0Cr21Al6 stainless steel cold-rolled sheet into a 10 mm x 10 mm sample after oxidation at 1000 °C for 500 hours.

[0024] 2. Select a section for mechanical polishing. Use 400, 800, 1200, and 2000 sandpaper for rough grinding and fine grinding, and finally use 1μm diamond polishing paste for polishing until the observation surface shows a mirror-like smooth effect.

[0025] 3. Use an ultrasonic cleaner to clean the sample with analytical pure anhydrous ethanol with a concentration of ≥99.7% for 2 minutes, and dry it with a hair dryer after taking it out.

[0026] 4. Use the IB-19530CP argon ion cross-section polisher produced by JEOL, Japan, to perform argon ion polishing of the mechanically polished cross section. The main parameter settings of argon ion polishing include: (1) acceleration voltage: 10KV, (2) sample chamber vacuum: 2×10 -4Pa, (3) the argon gas flow is optimized and set to 5.2, (4) the sample stage swing mode is turned on, (5) the polishing process is observed by camera, after about 30 minutes, the cross-section oxide scale is completely exposed, and about half of the plate cross-section after 1.0 mm has been argon ion polished, and then it stops.

[0027] 5. The sample after argon ion polishing is fixed on the sample stage of the scanning electron microscope, with the polished surface facing up. Using backscattered electrons for imaging, from the backscattered electron image obtained at 10,000 times, it can be seen that the oxide layer has a darker contrast than the substrate, and has a clear boundary with the stainless steel substrate. It is easy to measure that the average thickness of the oxide layer is 6.8 microns.

[0028] 6. The sample after argon ion polishing was fixed on a sample stage pre-tilted at 70°, and the EBSD test of the oxide layer was performed under a scanning electron microscope to analyze the phase composition and grain size. The main parameter selections were: (1) acceleration voltage 20KV, (2) probe current greater than 6.4nA, (3) magnification 10000 times, (4) measurement step length 0.05 microns, (5) the phase calibration results were Fe-Bcc, Alumina (alpha) and MgAl2O4. The stainless steel matrix was Fe-Bcc phase, the oxide layer was mainly Alumina (alpha), and there was a small amount of MgAl2O4 phase near the surface of the oxide layer.

[0029] The aluminum oxide grains in the oxide layer show columnar crystal characteristics near the substrate side, with an average grain size of 1.3 microns, while they show equiaxed crystal characteristics near the surface, with an average grain size of 0.9 microns. Example 2

[0030] Analysis of the cross-sectional structure of the oxide scale on 0Cr25Al5 cold-rolled stainless steel sheet after being kept at 1000℃ for 500 hours.

[0031] An oxidation experiment was carried out in the laboratory using 0Cr25Al5 stainless steel cold-rolled plates with a thickness of 1.2 mm. The plates were kept at 1000°C for 500 hours and then air-cooled.

[0032] The cross-sectional structure of the oxide scale is analyzed by the present invention, and the specific process is as follows: 1. Cut the 1.0 mm 0Cr25Al5 stainless steel cold-rolled sheet into a 10 mm × 11 mm sample after high temperature oxidation at 1000 °C for 500 hours.

[0033] 2. Select a section for mechanical polishing. Use 400, 800, 1200, and 2000 sandpaper for rough grinding and fine grinding, and finally use 1μm diamond polishing paste for polishing until the observation surface shows a mirror-like smooth effect.

[0034] 3. Use an ultrasonic cleaner to clean the sample with analytical pure anhydrous ethanol with a concentration of ≥99.7% for 3 minutes, and then dry it with a hair dryer.

[0035] 4. Use the IB-19530CP argon ion cross-section polisher produced by JEOL, Japan, to perform argon ion polishing of the mechanically polished cross section. The main parameter settings of argon ion polishing include: (1) acceleration voltage: 9KV, (2) sample chamber vacuum: 2×10 -4 Pa, (3) the argon gas flow is optimized and set to 5.0, (4) the sample stage rocking mode is turned on, and (5) the polishing process is observed by camera. After about 35 minutes, the cross-section oxide scale is completely exposed and then the polishing is stopped.

[0036] 5. The sample after argon ion polishing is fixed on the sample stage of the scanning electron microscope, with the polished surface facing up. Using backscattered electrons for imaging, the oxide layer has a darker contrast than the substrate, and has a clear boundary with the stainless steel substrate. It is easy to measure the average thickness of the oxide layer to be 7.1 microns.

[0037] 6. The sample after argon ion polishing was fixed on a sample stage pre-tilted at 70 degrees, and the EBSD test of the oxide layer was performed under a scanning electron microscope to analyze the phase composition and grain size. The main parameter selections were: (1) acceleration voltage 20KV, (2) probe current 13nA, (3) magnification 10000 times, (4) measurement step length 0.05 microns, (5) the phase calibration results were Fe-Bcc, Alumina (alpha) and MgAl2O4. The stainless steel matrix was Fe-Bcc phase, the oxide layer was mainly Alumina (alpha), and there was a small amount of MgAl2O4 phase near the surface of the oxide layer.

[0038] The aluminum oxide grains in the oxide layer show columnar crystal characteristics near the substrate side, with an average grain size of 1.5 microns, while they show equiaxed crystal characteristics near the surface, with an average grain size of 1.0 microns.

[0039] The above description is only a specific embodiment of the present invention, but the structural features of the protection scope of the present invention are not limited thereto. Any changes or modifications made by any technician in the field of the present invention are all covered by the patent scope of the present invention.

Claims

1. A method for analyzing the cross-sectional structure of high-temperature oxide scale of an iron-chromium-aluminum stainless steel plate, characterized in that: The following steps are involved: Step 1: Cut a sample from the high-temperature oxidized iron-chromium-aluminum stainless steel plate using a wire cutting method; Step 2: randomly select a cross section for mechanical polishing; Step 3: Use an ultrasonic cleaner to clean the sample with anhydrous ethanol with a concentration of ≥99.7% analytical grade for 2-5 minutes, and then let it air dry naturally or use a hair dryer to dry it; Step 4: Use an argon ion cross-section polisher to polish the mechanically polished cross section with argon ions. The parameters of argon ion polishing are as follows: acceleration voltage: 8-10KV, sample chamber vacuum: 1×10 -4 Pa-4×10 -4 Pa, argon flow rate is 1.0-3.0L / min, polishing time is 30-60 minutes; Step 5: Fix the sample after argon ion polishing on the sample stage of the scanning electron microscope with the polished surface facing up, and use backscattered electrons for imaging. Due to the thin thickness of the oxide layer, it is necessary to take pictures at 5000-20000 times to obtain an atomic number contrast image; Step 6: Fix the sample after argon ion polishing on a sample stage pre-tilted at 70 degrees, perform EBSD test on the oxide layer under a scanning electron microscope, analyze the phase composition and grain size, and select the following parameters: acceleration voltage 20KV, probe current 6.4nA-26nA, magnification 5000-20000 times, and measurement step length 0.02-0.1 microns.

2. The method for analyzing the cross-sectional structure of high-temperature oxide scale of an iron-chromium-aluminum stainless steel plate according to claim 1, characterized in that: In step 1, the temperature of high temperature oxidation is 900° C.-1300° C., the oxidation time is 100 hours-1000 hours, and the sample length is 8-12 mm and the width is 8-12 mm.